Cumplimiento de garantía procesal en procedimiento coactivo por parte de empresas públicas - Wasbrum Tinoco, Wilfrido Giovanny (2018)
The present study intends to demonstrate that in Ecuador the guarantees established in the law and in the constitution for the coercive enforcement procedure applied by the public companies are not respected. This can be seen in the processes initiated and executed by public companies on a daily basis, we refer specifically in this study to processes in which there is no due notification in a timely manner, which violates the defendants' right to defense. The work is based on the criterion that any failure to comply with a procedure established in the law by an official derives directly or indirectly from the violation of a constitutional guarantee in the last instance, a criterion manifested by many jurists who have known of these procedures and the negative implications that they entail when not respecting the guarantees of the accused……..